Local Economic Development Strategy to Increase the Competitiveness of MSMEs in the Tembe Nggoli (Typical Bima Woven Cloth) Creative Business in Ntobo Village, Bima City - Zanjabil Al A’Raaf; Iwan Harsono; Wahidin Wahidin (Experimental Student Experiences, 2023)
This research aims to analyze the influence of weaving MSMEs in improving the local economy in the community of Ntobo Village, Raba District, Bima City. This type of research is descriptive qualitative. Tests were carried out on SMEs that produce tembe nggoli (woven cloth) in the Ntobo Village area, Raba District, Bima City. The data used in this study are primary and secondary data. With data collection techniques are questionnaires and documentation. The data analysis method uses ANP analysis and SWOT analysis to help solve a problem in increasing production and developing the local economy in Tembe Nggoli (woven fabric) MSMEs. The results of the analysis show that to help improve the local economy and the competitiveness of Tembe Nggoli (woven fabric) products, woven fabrics are needed to have quality, varied motifs, promotional support and government assistance, affordable prices for all levels of society, both low, middle and upper economic groups. , so that it can prevent obstacles to increasing weaving production among MSMEs in Ntobo Village and strategically develop the local economy.